Different Brain Responses to Pain and Its Expectation in the Dental Chair. (July 2015) - Racek, A.J.; Hu, X.; Nascimento, T.D.; Bender, M.C.; Khatib, L.; Chiego, D.; Holland, G.R.; Bauer, P.; McDonald, N.; Ellwood, R.P.; DaSilva, A.F.
A dental appointment commonly prompts fear of a painful experience, yet we have never fully understood how our brains react to the expectation of imminent tooth pain once in a dental chair. In our study, 21 patients with hypersensitive teeth were tested using nonpainful and painful stimuli in a clinical setting. Subjects were tested in a dental chair using functional near-infrared spectroscopy to measure cortical activity during a stepwise cold stimulation of a hypersensitive tooth, as well as nonpainful control stimulation on the same tooth. Patients' sensory-discriminative and emotional-cognitive cortical regions were studied through the transition of a neutral to a painful stimulation. In the putative somatosensory cortex contralateral to the stimulus, 2 well-defined hemodynamic peaks were detected in the homuncular orofacial region: the first peak during the nonpainful phase and a second peak after the pain threshold was reached. Moreover, in the upper-left and lower-right prefrontal cortices, there was a significant active hemodynamic response in only the first phase, before the pain. Subsequently, the same prefrontal cortical areas deactivated after a painful experience had been reached. Our study indicates for the first time that pain perception and expectation elicit different hemodynamic cortical responses in a dental clinical setting.